APPLYING KAHOOT TO LEAR VOCABULARY - Nelvia Ibrahim (Jurnal Cakrawala Ilmiah, 2025)
The advancement of technology has improved the implementation of gamification in various educational settings. Gamification has been implemented in numerous educational settings as technology has advanced. Kahoot is a digital game-based learning platform that is becoming more and more incorporated into educational settings to enhance classroom learning and it can be increasingly to boost classroom learning. It is hoped that this can be applied by the students in learning vocabulary also they can practice it with more cheerful and enjoyment.